IEEE 802.11ah Network Planning for IoT Smart Meter Application: Case Study in Bandung Area - Fachri Nugraha Adhiatma; Doan Perdana; Nachwan Mufti Adriansyah; Risqi Herlambang Raharjo (Jurnal Pekommas, 2020)
The growth of Wireless Fidelity (WiFi) technology is so rapid and popular. The technology most widely used for WiFi services is the IEEE 802.11 family of standards. To support the Internet of Things (IoT) era, 802.11ah standard technology has developed, and the standard is intended to provide a low-cost mode of operation, with a wider coverage area, and can support thousands of devices per cell. This paper discusses IEEE 802.11ah Standard Network Planning for the Internet of Things Application (Case Study: Smart Meter Using WiFi.id Network in Bandung), to improve network quality in terms of coverage and capacity to improve the efficiency of the WiFi network and so that it can supports the Internet of Things (IoT) service. Network planning using 802.11ah for the internet of things application with a smart meter case study using the WiFi.id network has been successfully carried out. To cover the entire area of Bandung, 23 sites are required. In the capacity, the Tx slots needed to cover possible smart meters for each site are only 9 tx slots out of a total of 100 tx slots.